PELATIHAN DAN PENYULUHAN PENDIRIAN BUMDES DAN KOPERASI PADA KELOMPOK TANI DESA PESISIR BUKIT, KECAMATAN GUNUNG TUJUH, KABUPATEN KERINCI - Idrus, Ali; Setiyadi, Bradley; Denmar, Denny; Pratama, Robin (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2021)
Agricultural development policies are implemented to improve food security, develop agribusiness, and improve farmers' welfare so that the agricultural products produced must meet the requirements for quantity, quality, and sustainability, as well as being competitive and easy to obtain at affordable prices. The potential that exists in the form of food agricultural products, horticultural plantations, livestock, and agro-tourism development needs to be managed properly through the existence of BUMDes and village cooperatives. Therefore, mentoring activities, in the form of training and counseling on the procedures for establishing BUMDes and cooperatives for the sustainability of agricultural product management, both pre- and post-harvest. This service will provide training and counseling to farmer groups in Pesisir Bukit Village, Kerinci Regency, so that they can establish BUMDes and cooperatives to increase agricultural commodity yields and develop village potential. The end result of this service activity is that farmers can manage agricultural products and develop village potential through BUMDes and cooperatives so that they have an impact on improving living standards.